Composite films with low dielectric constant and dielectric loss factor at high frequency prepared from polyimide and polytetrafluoroethylene. Issue 12 (29th October 2022) - Zhang, Wang; Jiang, Hanzhou; Nie, Yong; Fang, Xingzhong; Chen, Guofei
Abstract: A series of polyimide/polytetrafluoroethylene (PI/PTFE) hybrid films were synthesized by blending water‐soluble polyamide acid salts with water‐based PTFE dispersion and thermal imidization to enhance the dielectric proprieties of PI. The relationship between PTFE filler content and the properties of films has been investigated. The results showed that the dielectric properties of PI were effectively improved by PTFE fillers and all films showed excellent heat resistance. When the addition of PTFE filler was 30 wt%, the PI and PTFE in PI/PTFE‐30 hybrid film still showed good compatibility and dispersity. The dielectric constant and dielectric loss factor were decreased to 2.42 and 0.0044 at 10 GHz, respectively. Meanwhile, the film PI/PTFE‐30 had the lowest water absorption (0.11%) and maximum water contact angle (95.3°). Abstract : Polyimide/PTFE hybrid films with low dielectric constantand dielectric loss factor are prepared by aqueous solution blending method .